A Case Report: Ovarian Sertoli-Leydig Cell Tumor With Hyperestrogenism and Endometrial Hyperplasia in a Postmenopausal Woman. (10th March 2017) - Tsuzuki, Yoko; Kikuchi, Iwaho; Nojima, Michio; Yoshida, Koyo; Hashizume, Akane; Tomita, Shigeki
The patient was a 66-year-old woman, G2P2. The patient presented a chief complaint of irregular postmenopausal bleeding 1 month ago. A transvaginal ultrasonography showed that bilateral ovaries were not enlarged and uterine endometrium was thickened, measuring at 9 mm. As a result of endometrial curettage, the simple endometrial hyperplasia was revealed. A blood examination showed an elevated estradiol level of 67 pg/mL, an elevated level of testosterone 0.64 ng/mL, and a slightly suppressed follicle-stimulating hormone (FSH) level of 34.86 mIU/mL. We conducted laparoscopic hysterectomy and bilateral salpingo-oophorectomy because the patient strongly suggested less invasive surgery. The result of pathological diagnosis was Sertoli-Leydig cell tumor (SLCT) in moderately differentiation. A blood examination after a month postoperatively revealed an elevated FSH level of 85.59 mIU/mL, depressed estradiol level of less than 10 pg/mL, and testosterone level of less than 0.03 ng/mL. There was no evidence of recurrence in the first year of follow-up.